Atypical depression in the structure of organic mental disorders (literature review). - Spirina, I. D.; Leonov, S. F.; Shusterman, T. Y.; Rokutov, S. V.; Shornikov, A. V. (Medicni Perspektivi, 2014)
The review of literature presents current data on clinical picture and diagnostics of atypical depression. Rubric “atypical depression” includes a variety of depressive states characterized by reactively caused changes of mood, sensitivity to interpersonal contacts, inverted vegetative and somatic symptoms such as increased appetite and hypersomnia. The article considers the place of atypical depression in the structure of organic mental disorders. Positions of foreign authors that produce atypical depression as a clinical entity in the structure of Bipolar affective disorder II type are represented, the views of other authors on the structure of atypical depression are considered. The analysis of national concept of non-circular depression is carried out. Questions of atypical affective conditions acquire special significance due to preparation of International Classification of Diseases of the 11th revision, because inclusion in it of Bipolar affective disorder II type, a manifestation of which is considered to be atypical depressions, is under discussion.